A relação criança e natureza na educação infantil a partir da pedagogia Waldorf: aproximações na formação inicial em pedagogia da UFS – campus Itabaiana - Santana, Josiene de Carvalho (2023)
The relationship between society and nature is marked by conceptions and practices that are increasingly overwhelming in the way they consume nature. Knowing that it is through education that human beings find the means to build knowledge and transform the way they relate to life, the general objective of this research is to analyze how Waldorf Pedagogy conceives the relationship between children and nature at the Early Childhood Education stage, considering the education of students on the Pedagogy course at UFS, Itabaiana Campus. In order to do this, the educational principles and foundations of WBS were listed, the relationship between child and nature in the educational context of WBS was identified, and a proposal for a university extension course was developed and implemented with 23 Pedagogy students from the UFS Itabaiana Campus as a creative possibility for intervention. The research was qualitative, participant-based and used questionnaires to analyze the understanding of the students during the course. Understanding that the future depends on the care we give to early childhood, the main findings point to the foundation of PW as part of an Anthroposophical worldview, based on the epistemological parameters of a deep ecology that understands the human being as a harmonious physical-animal-spiritual unity. It is also understood that the principles and foundations of PW are based on an educational practice consisting of both bodily, cognitive and emotional skills; the pedagogical approach is closely linked to the rhythms and cycles of nature, as well as cultural celebrations; and the bonds that children build with nature are formed in everyday life, through a multiplicity of direct experiences in nature, articulating the society/nature relationship from an early age. In addition, the participant intervention in the extension course based on the principles and practices of PW mobilized the appropriation of concepts by Pedagogy students, in a playful and light-hearted way, generating a significant impact on the construction of a pedagogical practice that values the relationship between children and nature from Early Childhood Education. In addition, the course guidelines based on Waldorf Pedagogy will be accessible to the public as an educational product of the research, allowing educators to apply them in their educational practices.